Domperidone Withdrawal in a Nursing Female with Pre-existing Psychiatric Illness: A Case Report - Sharma, Verinder; Sharma, Sapna; Doobay, Minakshi (Current Drug Safety, 2022)
Background: In this report, we describe a case of domperidone withdrawal in a woman with a history of major depressive disorder and obsessive-compulsive disorder (OCD), who experienced a recurrence of these disorders after stopping domperidone. Case Presentation: The symptoms improved after the restarting of domperidone and disappeared gradually as the drug was tapered and discontinued. Clinicians should consider domperidone withdrawal a differential diagnosis in women with a history of depression or anxiety who present with an acute onset of these symptoms following the abrupt discontinuation of domperidone. Conclusion: A gradual taper off of the drug may be effective in minimizing withdrawal symptoms and obviate the need for psychotropic drug use.
Keywords: galactagogue